KARAKTERISASI PALA (Myristica fragrans L.) DI KABUPATEN KEPULAUAN SANGIHE BERDASARKAN MORFOLOGI BUAH DAN DAUN - Widya Lusye Legoh; Semuel Runtunuwu; Sesilia Wanget (Sam Ratulangi University, 2020)
This study aims to characterize nutmeg in Sangihe based on the morphology of leaves and fruit. The research was carried out in the Sangihe Islands District from April to August 2019. The research was conducted in six sub-districts and two villages were selected as each research location. The six sub-districts with two villages per sub-district were Sub-district of Tabukan Selatan (Lesabe Village and Malamenggu Village), Sub-district of Kendahe (Kendahe 1 Village and Kendahe 2 Village), Sub-district of Manganitu (Taloarane Village and Bakalaeng Village), Sub-district of Tabukan Selatan Tengah (Hangke Village and Salurang Village), Sub-district of Tamako (Balane Village and Upel Village) Sub-district of Tahuna Barat (Pananekeng Village and Angges Village). Using the direct survey method in the farmers' nutmeg area. Next, the selection of nutmeg plants aged 15 years and above that has fruitful and healthy trees. After that the observations were made on the morphology of the selected nutmeg fruits and leaves. Variables observed were: leaf shape, leaf color, fruit shape, fruit skin color, fruit flesh color, mace color, fruit length, fruit diameter, seed fresh weight, seed length, seed diameter, mace fresh weight. The data obtained were analyzed quantitatively and qualitatively. The results of the study showed that the shape of nutmeg on Sangihe Island consisted of round and long, the leaf shape consisted of elongated round and between long jorong and round leaves, the leaf color consisted of green and dark green, the shape of round and elliptic seeds, the color of red mace , white fruit flesh color, yellow fruit skin color, the highest average fresh fruit weight is in Balane Village (59.41 g), the highest average seed weight is in Malamenggu Village (9.90 g), average fresh weight the highest mace is found in Lesabe Village (1.73 g).*eprm*